Prelude to the Crisis: The US Treasury, Financial Markets and 'Failure Containment'. (September 2014) - Panitch, Leo; Gindin, Sam
This article traces the central role of the American state, led by the Treasury, not only in the spread and deepening of global finance, but also in containing the financial crises to which this gave rise. The first part examines this role in relation to the financial crises abroad in the 1990s. The second part focuses on the Treasury's opting for failure containment over failure prevention amidst the financialization it promoted through the 1990s. The third part shows how this laid the basis for the interpenetration of US and foreign financial markets in the mortgage credit boom in the years leading up to the 2007 financial crisis.